Triple ectopic thyroid-a rare case report - G., Ashok Kumar; Arumugam, Murugan; S., Manoj Karthik; Nilakanta, Ananthakrishnan (International Surgery Journal, 2021)
The ectopic tissue of the thyroid gland along the descent of thyroglossal duct is a rare congenital aberration with or without the presence of normal thyroid gland. Single or dual ectopic thyroid has been reported. Three ectopic focuses at different locations are extremely rare. We present a rare case report of twenty years old female who presented with swelling over the anterior aspect of the neck mimicking thyroglossal cyst. Up on imaging evaluation ectopic thyroid at three different levels were diagnosed by computed tomography (CT) neck. Hence surgery was avoided and patient was managed with thyroxine supplement and follow up.